Determinants of knowledge sharing of management accounting information among decision makers / Wee Shu Hui - Wee, Shu Hui (Research Management Institute (RMI), 2013)
In our current economic situation, business activities are said to be knowledge-demanding. The awareness of companies on the importance of managing individual and collective knowledge has increased. There are high requirements of knowledge in the knowledge driven economy where specialized expert knowledge and problem solving know-how are crucial to bring a firm towards better performance. Most organizations have valuable knowledge contributing to better processes, management and technologies. Better processing and lower cost are among the determinants for high performance of a company. Knowledge is considered as one of the intellectual materials in organizations that could create wealth. This is known as the intellectual capital where it can create assets of higher value (Kannan and Aulbur, 2004). Consequently, the involvement of management accountants in the knowledge sharing process is very crucial. A research by Edward, Collier and Shaw (2005) shows that their role is to identify the essential knowledge, develop, utilize and analyze the knowledge for the organization to the benefit of the business performance. A performance measurement process would assist the company to achieve its strategic goals that would lead towards high performance. Many companies consider knowledge as vital resources for contributing to management and competitiveness. This research to focus and explores on the aspects of knowledge sharing with the influencing factors and also determine its relationship with the business performance of companies in Malaysia. The main two influencing factors identifies in this research are individual factors and organizational factors. Research results from the survey of 119 respondents from several organizations in Malaysia show that individual factors and organizational factors are positively influence the willingness of employees to donate and collect knowledge. Findings also show that knowledge sharing processes have positive influence of the overall business performance.